Progress on neuromodulation for treatment of central pain - GAN Yu; WAN Jun⁃ge; LI Zhong⁃hua; LI Shuai; HAN Shuai (Chinese Journal of Contemporary Neurology and Neurosurgery)
Central pain often arises as a sequela of lesions in the central somatosensory nervous system, and the intensity of pain is generally severe, significantly impacting patients' quality of life. Conventional pharmacological therapies usually have limited efficacy. In recent years, neuromodulation technique mainly including spinal cord stimulation (SCS) and motor cortex stimulation (MCS), which have been widely applied in the treatment of central pain. This review provides an overview of the two techniques in terms of their principles, clinical applications and adverse effects, and analyze the future research directions, aiming to guide the application of neuromodulation technique in central pain.